Measuring the impact of road infrastructure on household well-being: Evidence from Azerbaijan - Nurmukhammad Yusupov (Asian Development Bank Institute (ADBI), 2020)
Infrastructure is often seen as a critical factor in economic development. However, impact assessment for infrastructure projects is a challenge due to a number of methodological issues. Both developing economies and countries in transition could benefit from such studies to better inform their future policies. In this paper, we assess the impact of road construction on some aspects of household financial wealth in the target communities in Azerbaijan. To that end, we construct a two-wave data set with regional data and household characteristics, spanning the course of eight years, and estimate the differentials created by regional-level access to national roads. The results show that road treatment increased monthly rent by AZN83-AZN110 per month, which is 50%-60% of the mean monthly rent in the baseline year. Also, the self-assessed wealth increased by 0.9 to 3.1 units as a result of road construction, which is economically significant. Our study finds that gaining access to roads does indeed have a positive effect on financial wealth in some contexts. This may have implications for the selection of target communities or spatial sequencing in the infrastructure improvement efforts of policy makers.
Keywords: O18; P23; G51; 330; infrastructure; development; transition economies; Azerbaijan; household welfare